2015
DOI: 10.1038/nsmb.2999
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of integrin inactivation by filamin

Abstract: The activation of heterodimeric (α/β) integrin is crucial for regulating cell adhesion. Binding of talin to the cytoplasmic face of integrin activates the receptor, but how integrin is properly maintained in resting state to counterbalance its activation for regulating adhesion dynamics remains obscure. We report the structure of cytoplasmic domain of human integrin αIIbβ3 bound to its inhibitor, the immunoglobin repeat 21 of filamin A (FLNa-Ig21). The structure reveals an unexpected ternary complex where FLNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 41 publications
4
91
0
Order By: Relevance
“…Filamin A can interact with the cytoplasmic tail of integrin 3 via its Ig-like domain 21 (FLNa21), but FLNa21 can also bind to the linker between FLNa20 and 21 in an intramolecular complex that competes with integrin. Intriguingly, the removal of the trans -complemented β-strand from FLNa21 unmasks the binding site for integrin, which, when bound to filamin, engages integrin an inactive state (Heikkinen et al., 2009, Liu et al., 2015). This specific interaction can be opened by mechanical stretch and triggers integrin binding, filamin's partner in mechanosensing (Chen et al., 2009, Seppala et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Filamin A can interact with the cytoplasmic tail of integrin 3 via its Ig-like domain 21 (FLNa21), but FLNa21 can also bind to the linker between FLNa20 and 21 in an intramolecular complex that competes with integrin. Intriguingly, the removal of the trans -complemented β-strand from FLNa21 unmasks the binding site for integrin, which, when bound to filamin, engages integrin an inactive state (Heikkinen et al., 2009, Liu et al., 2015). This specific interaction can be opened by mechanical stretch and triggers integrin binding, filamin's partner in mechanosensing (Chen et al., 2009, Seppala et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It does so in part by phosphorylating its target FLNa, a negative regulator of integrin activation [36, 47], and promoting FLNa association with the integrin cytoplasmic tails. We now find that RSK2 alters adhesion and migration in GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also consistent with this view, the actin-binding site of FLNa that is responsible for its actin cross-linking activity was not required to sustain efficient recycling of CCR2B and β2AR. Based on our current observations and previous data demonstrating that FLNa interacts with several chemokine receptors and integrins (Liu et al, 2015), which follow the same path to the plasma membrane, we propose that FLNa works as a receptor scaffold that links cargo directly or indirectly to actin microdomains in the sorting endosome. We found that this FLNa function is regulated by its phosphorylation at S2152, which, in turn, is promoted by GPCR-signaling to second messenger kinases.…”
Section: Discussionmentioning
confidence: 99%